Whole‐exome sequencing of T‐B+ severe combined immunodeficiency in Egyptian infants, JAK3 predominance and novel variants. (2nd November 2020) - El Hawary, R.; Meshaal, S.; Mauracher, A.A.; Opitz, L.; Abd Elaziz, D.; Lotfy, S.; Eldash, A.; Boutros, J.; Galal, N.; Pachlopnik Schmid, J.; Elmarsafy, A.
Summary: Severe combined immunodeficiency (SCID) is fatal if not treated with immune reconstitution. In Egypt, T ‐ B + SCID accounts for 38·5% of SCID diagnoses. An accurate genetic diagnosis is essential for choosing appropriate treatment modalities and for offering genetic counseling to the patient's family. The objectives of this study were to describe the clinical, immunological and molecular characteristics of a cohort of twenty Egyptian patients with T ‐ B + SCID. The initial diagnosis (based on clinical features and flow cytometry) was followed by molecular investigation (whole‐exome sequencing). All patients had the classic clinical picture for SCID, including failure to thrive ( n = 20), oral candidiasis ( n = 17), persistent diarrhea ( n = 14), pneumonia ( n = 13), napkin dermatitis ( n = 10), skin rash ( n = 7), otitis media ( n = 3) and meningitis ( n = 2). The onset of manifestations was at the age of 2·4 ± 1·6 months and diagnosis at the age of 6·7 ± ·5 months, giving a diagnostic delay of 4·3 months. JAK 3 gene variants were most frequent ( n = 12) with three novel variants identified, followed by IL2R γ variants ( n = 6) with two novel variants. IL7Rα and CD3ε variants were found once, with a novel variant each. T ‐ B + NK − SCID accounted for approximately 90% of the Egyptian patients with T ‐ B + SCID. Of these T ‐ B + NK − SCID cases, 60% were autosomal recessive syndromes caused by JAK3 mutations and 30% were X‐linked syndromes. It might be useful to sequence the JAK3 gene (i.e. targeted Sanger sequencing) in all T ‐ B + SCID patients, especially after X‐linked SCID has been ruled out. Hence, no more than 10% of T ‐ B + SCID patients might require next‐generation for a molecular diagnosis. Abstract : The clinical manifestations in the T ‐ B + SCID patients includes failure to thrive, oral ‎candidiasis, diarrhea, pneumonia, napkin dermatitis, skin rash, otitis media and ‎meningitis. ‎ Genetic analysis of T ‐ B + Egyptian SCID patients revealed variants in JAK3 gene in ‎‎60% of the patients, IL2RG in 30%, IL7RA in 5% and CD3E in 5%. ‎JAK3 gene should be sequenced in all T ‐ B + patients especially if X SCID is ruled out ‎in male patients by analyzing the family's pedigree, medical history and Sanger ‎sequencing.‎